On Finsler Geometry: Review of applications in Solid Mechanics and Air craft motion - Pooja SwaroopSaxena (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
In Finsler geometry, each point of a base manifold can be endowed with coordinates describing its position as well as a set of one or more vectors describing directions. Finsler geometry encompasses Riemannian, Euclidean, and Minkowskian geometries as special cases, and thus it affords great generality for describing a number of phenomena in physics. This paper is involving application of Finsler geometry in solid mechanics is reviewed. With the help of finsler Gauge transformation it has been shown the geometrization of Electromagnetism in Finsler spaces.